Evaluation of Plasmodium falciparum MSP10 and its development as a serological tool for the Peruvian Amazon region - Bendezu J. (2019)
Background: Different antigens are needed to characterize Plasmodium falciparum infection in terms of seroreactivity and targets for invasion inhibition, in order to guide and identify the proper use of such proteins as tools for the development of serological markers and/or as vaccine candidates. Methods: IgG responses in 84 serum samples from individuals with P. falciparum infection [classified as symptomatic (Sym) or asymptomatic (Asym)], or acute Plasmodium vivax infection, from the Peruvian Amazon region, were evaluated by enzyme-linked immunosorbent assays specific for a baculovirus-produced recombinant protein P. falciparum Merozoite Surface Protein 10 (rMSP10) and for non-EGF region selected peptides of PfMSP10 selected by a bioinformatics tool (PfMSP10-1, PfMSP10-2 and PfMSP10-3). Monoclonal antibodies against the selected peptides were evaluated by western blotting, confocal microscopy and inhibition invasion assays. Results: Seroreactivity analysis of the P. falciparum Sym-and Asym-infected individuals against rMSP10 showed a higher response as compared to the individuals with P. vivax acute infection. IgG responses against peptide PfMSP10-1 were weak. Interestingly high IgG response was found against peptide PfMSP10-2 and the combination of peptides PfMSP10-1 + PfMSP10-2. Monoclonal antibodies were capable of detecting native PfMSP10 on purified schizonts by western blot and confocal microscopy. A low percentage of inhibition of merozoite invasion of erythrocytes in vitro was observed when the monoclonal antibodies were compared with the control antibody against AMA-1 antigen. Further studies are needed to evaluate the role of PfMSP10 in the merozoite invasion. Conclusions: The rMSP10 and the PfMSP10-2 peptide synthesized for this study may be useful antigens for evaluation of P. falciparum malaria exposure in Sym and Asym individuals from the Peruvian Amazon region. Moreover, these antigens can be used for further investigation of the role of this protein in other malaria-endemic areas. © 2019 The Author(s).